Microbial Quality of Formulated Infant Milk Powders - Rajput, Imran Rashid; Khaskheli, M.; Rao, S.; Fazlani, S.A.; Shah, Q.A.; Khaskheli, G.B. (Pakistan Journal of Nutrition, 2009)
Study was carried out to examine the microbiological quality of Infant formula milk powder. Total 60 of dried milk powders, 20 each of Group A (1-6), B (7-12) and C (13-18 months). Infant formula milk powders were purchased from Hyderabad, Sindh and evaluated for microbiological examination, like Total Viable Count (TVC), Enterobacteriaceae Count (EbC) and Yeasts and Moulds Count (YMC). Total viable count, (3.4x103±5.0x102cfu/g) were significantly higher than thermoduric count, (